Clinical characteristics and prognosis of paraneoplastic syndromes: a single-center cohort study in Northern China - Hu, Minzhe; Wang, Qianchang; Xiao, Yuxiu; Qin, Danqing; Guo, Shougang; Wang, Chunjuan (Frontiers in Immunology, 2026)
PurposeTo explore the clinical features, treatment, and prognosis of paraneoplastic neurological syndromes (PNS).MethodsIn this retrospective cohort study, the records of 114 patients diagnosed with probable (n = 65) or definite (n = 49) PNS between July 2016 and October 2024 were analyzed. Short-term outcome was defined as the point decrease in modified Rankin Scale score from peak disease to discharge(Δmodified Rankin Scale). Long-term prognosis was determined by mortality at last follow-up. Prognostic factors were identified using logistic regression and Cox models. The impact of tumors and high-risk antibodies on survival were assessed by Kaplan–Meier curves.ResultsOf the 114 patients, 65 (57.0%) were males. The median age was 63 years. Muscle weakness (53.5%) was most common, followed by seizures and altered consciousness. Associated tumors occurred in 66.7% of patients, mainly lung (65.8%) and breast cancer (9.2%). Antibodies were detected in 79.8%, including (single and multiple antibody types) anti-GABABR (24.2%), anti-Hu (19.8%), and anti-SOX1 (19.8%). Multiple antibodies were detected in 18.4%, including anti-Hu plus anti-SOX1 (19.0%), anti-SOX1 plus anti-GABABR (14.3%), and others. Independent factors associated with short-term favorable outcome (Δmodified Rankin Scale ≥1) were age < 65 years(OR = 3.41, 95% CI: 1.45–7.98, P = 0.005), CNS involvement (OR = 2.46, 95% CI: 1.05–5.80, P = 0.039), and immunotherapy (OR = 5.12, 95% CI: 1.70–15.42, P = 0.004). The median survival was 32 months (IQR, 12–106), the 3-year survival rate was 45.8%. SCLC (HR = 3.04, 95% CI: 1.71–5.41, P < 0.001) and high-risk antibodies (HR = 2.06, 95% CI: 1.17–3.62, P = 0.012) were independently associated with higher mortality.ConclusionsAge < 65 years, CNS involvement and immunotherapy are relevant to favorable short-term outcome. SCLC and high-risk antibodies are adverse factors of long-term survival in PNS.